Enhancing firm performance through corporate strategy and religious observance: Implications for business sustainability - Kartono,; Johari, Razana Juhaida; Rosnidah, Ida; Hamdani, Emrizal (Edelweiss Applied Science and Technology, 2024)
This research aims to determine the influence of corporate strategy and religious observance on company performance and business sustainability. Apart from that, this research also examines the role of company performance in mediating the influence of corporate strategy and religious observance on business sustainability. This study utilized a quantitative descriptive with an explanatory research approach. The data was collected from the distribution of questionnaires to 125 respondents representing the Cirebon City Regional-owned Enterprise located in Cirebon, Indonesia. The PLS-SEM (Partial Least Square - Structural Equation Modeling) with the Smart PLS 3 data processing application has been used to analyze the proposed hypotheses. The research results show that corporate strategy and religious observance influence company performance and business sustainability. Apart from that, company performance was also found to mediate the influence of corporate strategy and religious observance on business sustainability. The results of this research can be used by the Regional Government of Cirebon City as the shareholder of Regional Owned Enterprises, especially Regional Pharmaceutical Companies, to implement corporate strategies and religious observance in managing human resources in their companies, because the research results show that these two factors can improve performance. Company and has a significant influence on employee performance, so that business continuity is also expected to be maintained.